An assessment of the role of the Ndebele ideological framework in promoting the philosophy of uBuntu - Moyo, Crispen (Midlands State University, 2020)
The concept of Ubuntu has been long existing in the Ndebele society, Zimbabwe and Africa as a whole. The concept has been existing since the pre-colonial times, yet little has been done to trace the contributions of the ideological frameworks which were used to promote the philosophy of Ubuntu. Hence the research work`s main aim was to assess the role of the Ndebele ideological framework in promoting the philosophy of Ubuntu. Evidence shows that the Ndebele traditional values played a crucial role in promoting Ubuntu within the Ndebele society. These traditional values were easily adopted by any age group without any difficulty in practicing those principles. There was no need for one to learn to read and write in order to have Ubuntu and also to understand these ideological frameworks. The research also indicates the impacts of Christianity on Ndebele traditions, practices and beliefs.